Study of efficacy of band ligation and suture ligation in the treatment of second degree hemorrhoids - Gole, S. N.; Toppo, Nitin; Poptani, Manoj (International Surgery Journal, 2021)
Background: Rubber band ligation (RBL) and suture ligation are treatment strategies adapted for management of second degree hemorrhoids, an anorectal condition leading to distal displacement of anal cushions. Aim of current study was to investigate efficacy of suture ligation and band ligation techniques used in management of grade two internal hemorrhoids in terms of intraoperative n post-operative complications. Methods: An observational prospective study was conducted on 108 patients presented with grade 2 internal heamorrhoids at JNM medical college, Raipur between 2018 to 2019. Patients were divided in two equal groups receiving rubber band and suture ligation as treatment approaches. Efficacy of both treatment approaches was studied in terms of post-operative complications observed at immediate, one week and one month follow-ups and on the basis of hospital stay time required. Results: Majority of patients in both the groups were males with most number of cases in age group of 31-40 years. There was no significant difference in dietary habits of patients in both group as well as efficacy of both treatment techniques. Post-operative pain, discomfort, prolapse were common complains in band ligation group with pain persisting even during one month follow-up. Pain, bleeding per rectum, discomfort and irritation per rectum were the most common post-operative complaints of suture ligation group during follow-up. Conclusions: Although efficacy of both treatment strategies were equivalent, RBL would be recommended over suture ligation treatment strategy due to requirement of regional anesthesia to reduce operative difficulty and more hospital stay time in suture ligation treatment strategy.